How proper measurement of low carbon hydrogen's carbon intensity can reduce regulatory risk - Alex Barnes (The Oxford Institute for Energy Studies, 2024)
Low carbon hydrogen (whether based on renewable or nuclear electricity, or fossil fuels with carbon capture) is a means to decarbonise sectors of the economy which are hard to electrify. Its business model is heavily dependent on government intervention (e.g. mandatory targets, subsidies, decarbonisation policies) so low carbon hydrogen is subject to significant regulatory risk. The boundary between low carbon hydrogen and electrification is not clear cut. Low carbon hydrogen needs to demonstrate that it is good value for money as a way to reduce emissions. This means not only the cost of low carbon hydrogen itself but also the cost of reducing emissions by using it. Current terminology for low carbon hydrogen (e.g 'blue', 'green', 'renewable', 'clean' etc) is confusing, as are the qualifying criteria. This paper examines the challenges facing stakeholders with regards to understanding hydrogen's carbon intensity; the confusing nomenclature applied to low carbon hydrogen; and the impact that different approaches to measuring carbon intensity can have on hydrogen costs and its actual carbon intensity. It then proposes ways in which regulatory risk can be reduced.
Keywords: 330; `blue’ hydrogen; Additionality; Australia; Carbon Intensity; Clean hydrogen; decarbonisation; Electrification; electrolyser; EU; GHG Emissions; green hydrogen; Hydrogen; low-carbon hydrogen; Natural gas; Nuclear; Regulatory risk; Renewable hydrogen; RFNBO; Temporal correlation; UK; USA